Correlation investigation of the brightness of GDE-grams using the methods of computer graphics and direct measurements - Dobrovolsky , Yu.; Prokhorov, H.; Diachenko, L.; Zukow, W.; Babelyuk, V.; Popovych, I. (Journal of Education, Health and Sport, 2022)
There are two methods of measuring the glow of a liquid under the conditions of gas-discharge imaging. This is a investigation of the brightness of GD-grams - a digital image of streamers created under these conditions, and a direct measurement of brightness using a luminometer, which is carried out during the formation of a streamer during a gas discharge. In the first case, the digital image is analyzed using computer graphics methods and certain software. In the second, the results of direct measurement are analyzed. We have analyzed these two methods using the example of the glow of water under the conditions of gas-discharge visualization. It is shown that with direct measurements the brightness values ​​are higher than when investigating the brightness of a digital image of the same streamer obtained in the same time period. Namely 1.5 cd/m2 and 1.7 cd/m2. The difference is 13% and significantly exceeds the measurement error of the brightness meter (± 7%). According to the results of our research, we suggest that, at the very least, when calibrating the devices that create the GDV-grams, use direct measurements of the glow of the liquid in photometric units. For example, in brightness units.